2015
DOI: 10.1657/aaar0014-097
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Five Year Record of Changes in Plant Cover on Tundra of Northeastern Alaska

Abstract: Northern Alaska has warmed over recent decades and satellite data indicate that vegetation productivity has increased. To document vegetation changes in the Arctic National Wildlife Refuge, we monitored plant cover at 27 plots between 1984 and 2009. These are among the oldest permanently marked and continuously monitored vegetation plots in the Arctic. We quantified percent cover of all plant species by line-point intercept sampling and assessed change over time for seven plant growth forms. Cover of bryophyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
1
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 57 publications
5
21
1
9
Order By: Relevance
“…S1), we suspect that long-term trends would be difficult to detect without regular sampling. Our projected patterns of forage biomass also did not mirror results from other studies that have quantified long-term increases in plant productivity in the Arctic, particularly for shrubs (Hill and Henry 2011, Elmendorf et al 2012, Fraser et al 2014, but see Jorgenson et al 2015). This difference likely stems in part from the relatively short duration of our study (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) compared to investigations evaluating vegetation trends since the 1980s.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…S1), we suspect that long-term trends would be difficult to detect without regular sampling. Our projected patterns of forage biomass also did not mirror results from other studies that have quantified long-term increases in plant productivity in the Arctic, particularly for shrubs (Hill and Henry 2011, Elmendorf et al 2012, Fraser et al 2014, but see Jorgenson et al 2015). This difference likely stems in part from the relatively short duration of our study (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) compared to investigations evaluating vegetation trends since the 1980s.…”
Section: Discussioncontrasting
confidence: 92%
“…Because our predicted values of N exhibited so much interannual variation ( Fig. Our projected patterns of forage biomass also did not mirror results from other studies that have quantified long-term increases in plant productivity in the Arctic, particularly for shrubs (Hill and Henry 2011, Elmendorf et al 2012, Fraser et al 2014, but see Jorgenson et al 2015). S1), we suspect that long-term trends would be difficult to detect without regular sampling.…”
Section: Discussionmentioning
confidence: 65%
“…Given the short growing season and the large abundance of perennial and evergreen species with conservative growth strategies in this system (Bliss & Petersen, ) plant communities likely shift slowly, rather than abruptly, in response to environmental change and resource availability (Camill & Clark, ; Dormann & Woodin, ). In addition, previous work in this region has shown that plant percent cover in this system is unlikely to change over short (e.g., <5 years) temporal scales (Jorgenson, Raynolds, Reynolds, & Benson, ).…”
Section: Methodsmentioning
confidence: 84%
“…) concurrent with evidence of increasing thermokarst disturbances in the western Arctic (Lantz and Kokelj , Jorgenson et al. , Segal et al. , Kokelj et al.…”
Section: Discussionmentioning
confidence: 84%